Environmental impact assessment of rapeseed production using the LCA method: Part two: Life cycle impact assessment - Kiš Ferenc; Đurišić-Mladenović Nataša; Marjanović-Jeromela Ana (Selekcija i Semenarstvo)
This constitutes the second segment of an environmental life cycle assessment (LCA) study on oilseed rape cultivation in the prevalent conditions of Vojvodina, Serbia. The paper presents the results of the life cycle impact assessment (LCIA) phase of the LCA. The functional unit (FU) is one hectare of agricultural land used for winter rapeseed cultivation, with a reference flow of 3,000 kg of seeds, representing the average yield per hectare. The assessment is focused on the rapeseed production chain, concluding with the transportation of oilseeds to regional silos. The environmental impact assessment employed the ReCiPe 2016 (H) LCIA method, using the OpenLCA software. The study found that the total damage to human health was estimated at 0.0048 DALY, while damage due to biodiversity loss was calculated as 0.0001 species per year. Additionally, the damage resulting from the exploitation of geological mineral reserves was determined to be 167 USD per FU. Notably, land occupation was identified as the primary contributor to biodiversity loss, accounting for 90% of the associated damage within the rapeseed production chain. Meanwhile, the life cycle of diesel fuel, the mineral fertilizer production chain, and nitrogen compound emissions from agricultural land collectively accounted for 74% of the damage to human health and 91% of the damage attributed to mineral resource consumption. On the midpoint level, the ReCiPe 2016 (H) LCIA method calculates results within 18 impact categories, including the impact on global warming and fossil fuel depletion. The cumulative impact of greenhouse gases (GHG) emitted in the rapeseed production chain is equivalent to the impact of 1,970 kg of carbon dioxide. The carbon footprint of rapeseed was estimated at 0.65 kg CO2 eq. per kg of rapeseed. In the production chain of 3,000 kg of rapeseed, 454 kg of oil equivalent is consumed, which means that approximately 6.93 MJ of energy from fossil sources is required to produce 1 kg of rapeseed under the prevalent conditions in Vojvodina. The ReCiPe 2016 method identified and assessed the impact of approximately 750 different emissions with adverse effects on the environment, as well as the impact of around 250 different forms of natural resources consumed or used in the rapeseed production chain. However, the results of the LCIA analysis show that only about ten elementary flows are responsible for over 90% of the total damage in specific protection areas. These primarily include air emissions (carbon dioxide, ammonia, nitrogen oxides, nitrous oxide, sulphur dioxide, and suspended particles), emissions of certain heavy metals into water and soil (hexavalent chromium and zinc), as well as the exploitation of some natural resources, notably arable land, natural gas, and crude oil. The results of the LCIA analysis can be utilized to identify processes and emissions where rationalization or improved control can yield the greatest environmental benefits. The most substantial environmental improvements are expected through the reduction of mineral fertilizer consumption per unit yield and the decrease in diesel fuel usage for field and transportation activities. Furthermore, enhanced control over emissions that contribute significantly to the adverse impacts of the rapeseed production chain can also lead to substantial environmental enhancements.